Functional Supplements for Managing Exercise-Induced Gastrointestinal Distress: A Focused Review for Athletes - Bazarewicz, Jakub; Adaśko, Grzegorz; Świda, Michał; Kubuj, Cezary; Mazur, Urszula; Ogonowska, Paulina; Dmowski, Daniel; Michalska, Anna; Waszak, Julia; Siwik, Marcin (Quality in Sport, 2025)
Introduction: Exercise-induced gastrointestinal (GI) distress is common among endurance and high-intensity athletes. Symptoms such as nausea, cramps, and diarrhea can impair performance and recovery. Functional supplements with anti-inflammatory and gut-supportive properties are being explored as complementary strategies. Objective: This review evaluates six functional supplements—probiotics, ginger, curcumin, berberine, black currant, and bovine colostrum—for their potential to reduce exercise-induced GI symptoms. Methods: Recent studies (2017–2025) were identified via PubMed and Scopus, prioritizing human trials in athletic or exercise settings. Clinical models such as IBS and heat stress were also considered where athlete-specific data were lacking. Results: Probiotics and bovine colostrum show the most consistent benefits for gut integrity and immune modulation. Ginger and curcumin offer anti-inflammatory and antioxidant support, while black currant and berberine show promise despite limited direct sports data. Effects vary by dose, strain, and supplementation duration. Conclusions: Functional supplements may aid in managing GI distress in athletes. However, standardized protocols and athlete-specific trials are needed. Personalized approaches based on symptom profiles and training cycles may optimize efficacy.